Mathematical Modelling of Inventory Costs in Supply Chains with Horizontal Cooperation - Zahara, Chasna; Mardlijah, Mardlijah (International Journal of Global Operations Research, 2024)
Efficiency in the supply chain has become very important for companies in the era of increasingly fierce business competition. This has encouraged some companies to start implementing the concept of collaboration between companies or commonly called horizontal cooperation. Horizontal cooperation is important because companies need to work together to manage complex supply chains. To manage production in a collaborative supply chain requires designing a cost-effective model. The design of this model is expected to optimise inventory costs to achieve common goals in horizontal cooperation. This model is a form of linear programme consisting of objective function and constraint function. The objective function is to minimise the inventory cost in a four-tier supply chain with horizontal cooperation on post-production final storage at the production level only. The model was tested with 3 suppliers, 3 materials, 3 factories, 4 products, 3 distributors, and 3 consumers. The model with horizontal cooperation resulted in a total inventory cost of 1,349,830. This amount is 8% lower than the total inventory cost without horizontal cooperation. Thus, horizontal cooperation in the supply chain drastically reduces inventory costs throughout the supply chain.